Maximum load influence on cardiovascular system among highly qualified weightlifters depending on sports experience - Chernogorov, D. N.; Matveev, Y. A.; Nazarova, I. V.; Cherkasova, G. M. (The Russian Journal of Physical Education and Sport, 2016)
The urgency of this research work is conditioned by the fact that highly qualified sportsmen constantly experience increased physical loads, which, undoubtedly, influence the anatomy and physiology of internal organs, first of all cardiovascular system (CVS), which in terms of long-term trainings leads to the state "Sports heart" formation. Materials. The influence determination of competitive load on the processes of depolarization- repolarization of cardiac myocytes among highly qualified weightlifters, depending on their sports experience. Research methods: scientific literature analysis and summarizing, the method of microalternation registration of electrcardiographic signal with the help of diagnostic system "Cardiovizor-06C", methods of mathematical statistics.Results: The most important and statistically valid decrease of "Myocardium" and "Rhythm" indices after competitive load was revealed with a parallel revelation of the shifts according to dispersion indices of detailing from G1 till G9.The increase of the most significant typical complexes of detailing were stated, which belong to possible pathology - "metabolic changes, which include electrolytic balance violation", "hypertrophy of one of ventricles, mainly of the left one" and "myocardial hypoxia" in a group of highly qualified weightlifters with experience of more than 10 years.Conclusion. The received result proves that maximum physical load during competitions, regardless of the respondents` experience, causes functional state shift of CVS in a form of the processes violation of depolarization- repolarization of cardiac myocytes and it can be regarded as the risk of metabolic changes development and electrolytic balance of myocardium violation among weightlifters.